Intervention Effect of Supportive Group Therapy and Physical Exercise on the Quality of Life of Cancer Patients - Dimitra Papastergiou; Dimitrios Kokaridas; Konstantinos Bonotis; Nikolaos Digelidis; Asterios Patsiaouras (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
Psychological distress is a multidimensional concern affecting patients' ability to cope with cancer, its physical symptoms, and treatments. This study examined the effect of an exercise program and a group psychotherapy program on the quality of life of Greek cancer patients. The sample consisted of 39 cancer patients (10 males and 29 females), assigned randomly in three groups of 13 patients each group, that is, a control, an exercise and a psychotherapy group. The duration of the training program for the individuals of the exercise group was 10 weeks at a frequency of two sessions per week, 60 minutes each session. The patients of the psychotherapy group received a 10 weeks' supportive-expressive group therapy, at a frequency of one time per week, of 90 minutes each meeting. The quality of life SF-36 questionnaire was administered to examine the short-term effect of both programs prior and after intervention on quality of life. Control group individuals did not participate in any program and they just filled in the SF-36 questionnaire prior and after intervention. Improvement in "vitality" (p = .006) and mental health subscale (p = .011) was statistically significant between pre and post measures in the supportive therapy group. All other domains exhibit no significant changes. In the exercise group, physical functioning, role functioning and emotional role values were also improved but not to the point to generate statistically significant results. The findings of the present study support the positive impact of psychotherapy intervention on vitality and mental health component of patients with cancer, followed in less extent by the beneficial effect of the exercise program.